The estimation of intensity of inflammatory alterations of blood in early postinfarction remodeling. (26th April 2021) - Leonova, I; Bykova, E; Boldueva, S; Ivanova, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Structural postinfarction abnormalities is connected with inflammation. For better understanding of pathogenesis of postinfarction remodeling, it was studied the intensity of inflammatory disorders in early postinfarction period. Purpose: Research of the intensity of inflammatory response in early postinfarction remodeling. Materials and methods: 772 of patients with myocardial infarction (MI) were examined. Clinical blood analysis was performed at admission and on the 5th day of MI, as well as immunological examination, Echocardiography. Results: In patients with end-diastolic diameter (EDD) of left ventricle (LV) ≥ 55 mm, 5 day MI white blood cells (WBC) level (8, 0 ±2, 1*109/l vs 7, 3 ± 1, 9*109/l, p = 0, 0001), absolute number of neutrophils (5, 0 ± 1, 7* 109/l vs 4, 5 ± 1, 4*109/l, p = 0, 0006) and monocytes (0, 64 ± 0, 30*109/l vs 0, 57 ± 0, 30*109/l, p = 0, 005) were higher compared patients with EDD ≤ 55 mm. The inflammatory alterations in patients with increased end-diastolic volume (EDV) and end-systolic volume (ESV) of left ventricle was similar. The LV EDD was correlated with WBC level (r = 0, 3; p = 0, 00002), also with absolute number of neutrophils (r = 0, 3; p = 0, 0002) and monocytes (r = 0, 3; p = 0, 007). The positive connection of EDV LF with level of WBC (r = 0, 3; P = 0, 007) and absolute number of neutrophils (r = 0, 3; p = 0, 0002) was revealed. The positive connection of ESV LV with absolute number of neutrophils (r = 0, 3, р=0, 04; accordingly). It should be noted that increase of ESD LV more 37mm was not accompanied by authentic increase of inflammatory factors, but the connection of ESV LV with Il-6 was noted (ρ=0, 3; р=0, 03). As far as contractive function of myocardium declined, it was registered the increase of neutrophils (neutrophils on the 5 day in EF 55% and more - 4, 5 ± 1, 4*109/l, EF 55-40% - 4, 8 ± 1, 5*109/l, EF less 40% - 5, 1 ± 2, 1*109/l, p = 0, 002), also in formation of areas of akinesia (neutrophils on the 1 days - 9, 2 ± 3, 3*109/l vs 8, 3 ± 3, 1*109/l, р=0, 05) and aneurysm of LV (5, 08 ± 1, 71*109/l vs 4, 52 ± 1, 48*109/l, р=0, 0006). It should be noticed that functional activity of monocytes in patients with aneurism of LV was lower than in patients without aneurism (CD14 0, 035 ± 0, 02*109/l vs 0, 049 ± 0, 02*109/l, р=0, 05). It appears important obtained data that with hypertrophy LV and diastolic disfunction was noticed authentic increase of lymphocytes, expressing the marker of apoptosis CD95 (0, 458 ± 0, 276*109/l vs 0, 335 ± 0, 155*109/l, р=0, 05; 0, 441 ± 0, 26*109/l vs 0, 342 ± 0, 21*109/л, р=0, 01, accordingly). Conclusion: The increased activity of inflammatory markers, decline of functional activity of monocytes, the elevation of apoptosis marker, associated with bigger intensity of postinfarction remodeling processes. The acute phase of inflammation is necessary stage of healing, but with long-term clinical case, excessive activation or alteration of functional activity of leukocytes can lead to growth of structural and electrical remodeling.